Supermarket revolution in Asia and emerging development strategies to include small farmers - Reardon, Thomas; Timmer, Peter C.; Minten, Bart (Proceedings of the National Academy of Sciences, 2012)
A “supermarket revolution” has occurred in developing countries in the past 2 decades. We focus on three specific issues that reflect the impact of this revolution, particularly in Asia: continuity in transformation, innovation in transformation, and unique development strategies. First, the record shows that the rapid growth observed in the early 2000s in China, Indonesia, Malaysia, and Thailand has continued, and the “newcomers”—India and Vietnam—have grown even faster. Although foreign direct investment has been important, the roles of domestic conglomerates and even state investment have been significant and unique. Second, Asia's supermarket revolution has exhibited unique pathways of retail diffusion and procurement system change. There has been “precocious” penetration of rural towns by rural supermarkets and rural business hubs, emergence of penetration of fresh produce retail that took much longer to initiate in other regions, and emergence of Asian retail developing-country multinational chains. In procurement, a symbiosis between modern retail and the emerging and consolidating modern food processing and logistics sectors has arisen. Third, several approaches are being tried to link small farmers to supermarkets. Some are unique to Asia, for example assembling into a “hub” or “platform” or “park” the various companies and services that link farmers to modern markets. Other approaches relatively new to Asia are found elsewhere, especially in Latin America, including “bringing modern markets to farmers” by establishing collection centers and multipronged collection cum service provision arrangements, and forming market cooperatives and farmer companies to help small farmers access supermarkets.